(untitled) (Ius Novum, 2019)
The aim of the article was to define the role of the legal culture in development of the standards of judges’ professional ethics, to indicate the most representative definitions of culture and legal culture, and to specify the most important characteristics of judges required both in their work and in private life. The discussion covers also the issue of the legitimacy and significance of elaborating the most important principles of the judges’ professional ethics in the form of a code both in the past and present. The article presents the problem of the prestige of the judicial profession as viewed by the general public, lawyers, students and judges themselves. The analyses of documents, literature, as well as the historical and statistical techniques were exploited in the article. As a result of the conducted analyses, it was recognized that legal culture is the “third” element between law and its use, by which it also fulfils a social-regulatory role. The legal culture of authorities that apply law should not be in contradiction with the general system of values and ought to serve the society. This is particularly important in the context of judicial independence, because nowadays more and more influence of politicians and various lobbies on the activity of the judges is observable. As a consequence, it leads to the instrumental use of the legal acts and makes the position of the judge not impeccable in terms of ethics. In turn, this state of affairs brings about a significant decline of public esteem for judges